All quiet on the western front - Firda, Richard Arthur (Twayne Publishers, 1993)
Provides in-depth analysis of the literary work All Quiet on the Western Front, as well as its importance and critical reception. Includes a chronology of the life and works of the author
Description based on print version record
Keywords: Remarque; Erich Maria; Im Westen nichts Neues; World War; 1914-1918